1981
DOI: 10.1002/qua.560190312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the structure and properties of ClF2 and Cl3 radicals by CNDO/2 and INDO methods

Abstract: The shape of the 21-valence-electron systems like the triatomic interhalogens is not well known due to lack of sufficient experimental and theoretical studies. So far only two such interhalogens, namely, CIF2 and C13, have been experimentally characterized [1,2]. Recently, Ungemach and Schaefer [ 3 ] have reported a b initio SCF calculations on CIF2 using basis sets ranging from minimal to extended plus polarized CI. Their best results indicate that the bond angle of this radical is 148.8", which compares favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio 15,[24][25][26] and semiempirical methods. 9,[27][28][29][30][31][32] Recently, additional interest in the trihalogens has been generated by novel time-resolved studies of the Br + I 2 reaction. 1,[33][34][35][36] From the results on this system, it appears that trihalogens, accessed through photodissociation of HX-YZ complexes, may be especially suitable for real-time studies of reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation